2018
DOI: 10.1142/s0217979218501102
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dielectric behavior of the PVC/BaTiO3composite in low-frequencies

Abstract: Polyvinyl chloride (PVC) is widely used as insulator in electrical engineering especially as cable insulation sheaths. In order to improve the dielectric properties, polymers are mixed with ceramics. In this paper, PVC composites with different weight percentages 2 wt.%, 5 wt.%, 8 wt.% and 10 wt.% were prepared and investigated. Loss index ([Formula: see text]) and dielectric constant ([Formula: see text]) have been measured using an impedance analyzer RLC. Fourier transform infrared (FTIR) spectroscopy, scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…SEM images indicated that the pure PVC acted as a host matrix material and BaTiO 3 particles are almost evenly distributed with minimum agglomeration. Figure 3 a for pure PVC revealed smooth surface morphology consistent with previous studies [ 18 , 19 , 20 , 21 ]. The distribution of fillers in 30% of BT content is more obvious than that of 10% and 20% of BT content in the host PVC matrix.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…SEM images indicated that the pure PVC acted as a host matrix material and BaTiO 3 particles are almost evenly distributed with minimum agglomeration. Figure 3 a for pure PVC revealed smooth surface morphology consistent with previous studies [ 18 , 19 , 20 , 21 ]. The distribution of fillers in 30% of BT content is more obvious than that of 10% and 20% of BT content in the host PVC matrix.…”
Section: Resultssupporting
confidence: 89%
“…The FTIR absorption spectra of BT, PVC and PVC/BT composite thick films with various BT content as fillers are shown in Figure 4a. For pure PVC, the characteristic absorption peaks of CH 2 deformation mode were observed at 1332 cm −1 , CH rocking mode at 1253 cm −1 , trans CH-wagging mode at 958 cm −1 , C-Cl stretching mode at 833 cm −1 and C is CH-wagging mode at 610 cm −1 , consistent with previous reports [18,21]. For pure BT, a broad peak is observed at 544 cm −1 due to the O-Ti-O vibration [28].…”
Section: Ftir Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Novel polymeric composites containing ceramic powders have been utilized in order to improve insulators' performance [8,[19][20][21][22]. After the doping process in the samples a broadening of the peak in the BF region occurs [23] (Figures 2 and 3). A peak appears in the curve of the dielectric constant and in parallel an inflection in the curve of the loss index under around 50Hz.…”
Section: Volume Resistivity and Average Breakdown Voltagementioning
confidence: 99%